2022
DOI: 10.3758/s13428-022-02015-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, reliable mobile assessment of affect-related motor processing

Abstract: Mobile technologies can be used for behavioral assessments to associate changes in behavior with environmental context and its influence on mental health and disease. Research on real-time motor control with a joystick, analyzed using a computational proportion-derivative (PD) modeling approach, has shown that model parameters can be estimated with high reliability and are related both to self-reported fear and to brain structures important for affective regulation, such as the anterior cingulate cortex. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Note that another way to obtain an upper bound on test-retest reliability is to compute split-half reliability, which, like parameter recovery, is not affected by longitudinal changes in behavior. Less than half of the studies reviewed here estimated split-half reliability (Price et al, 2019;Shahar et al, 2019;Brown et al, 2020Brown et al, , 2021Bruder et al, 2021;Xu and Stocco, 2021;Hitchcock et al, 2022a;Loosen et al, 2022;Howlett et al, 2022). While most of these studies found split-half reliability to be higher than test-retest reliability, those that used tasks involving trial-by-trial learning found split-half reliability to be similar or even lower for some parameters (Brown et al, 2020(Brown et al, , 2021Loosen et al, 2022).…”
Section: Model Simulations Can Provide An Upper Bound On Reliabilitymentioning
confidence: 79%
See 3 more Smart Citations
“…Note that another way to obtain an upper bound on test-retest reliability is to compute split-half reliability, which, like parameter recovery, is not affected by longitudinal changes in behavior. Less than half of the studies reviewed here estimated split-half reliability (Price et al, 2019;Shahar et al, 2019;Brown et al, 2020Brown et al, , 2021Bruder et al, 2021;Xu and Stocco, 2021;Hitchcock et al, 2022a;Loosen et al, 2022;Howlett et al, 2022). While most of these studies found split-half reliability to be higher than test-retest reliability, those that used tasks involving trial-by-trial learning found split-half reliability to be similar or even lower for some parameters (Brown et al, 2020(Brown et al, , 2021Loosen et al, 2022).…”
Section: Model Simulations Can Provide An Upper Bound On Reliabilitymentioning
confidence: 79%
“…For example, monitoring disease course, treatment response, or characterizing dynamic computational phenotypes requires longitudinal testing, likely involving batteries of tasks. To make frequent longitudinal testing feasible, it might be necessary to move exclusively to remote testing strategies such as smartphone-based tasks (Gillan and Rutledge, 2021;Zech et al, 2022;Pronk et al, 2022;Howlett et al, 2022). Another underappreciated challenge is engagement.…”
Section: Longitudinal Validity and The Dynamic Nature Of Mental Disor...mentioning
confidence: 99%
See 2 more Smart Citations